Integritas Auditor dan Peranannya Terhadap Pembentukan Komitmen Organisasi - Ella Anastasya Sinambela; Rahayu Mardikaningsih (Universitas Nusantara PGRI Kediri, 2021)
Every Public Accounting Firm employs auditors who have high professionalism and ethical behavior. Auditor is a profession that has a great responsibility not only to the client and his office but also to the public. Professional auditors will carry out their duties with sincerity and accuracy which will affect the quality of the resulting audit. Auditors must also maintain the reputation of the organization which is manifested in the form of organizational commitment. The development of organizational commitment can be determined by the integrity of each auditor in a public accounting firm. The purpose of this study is to determine the effect of auditor integrity on organizational commitment. This quantitative survey research uses auditors who work at the Surabaya Regional Public Accounting Firm as the research population. There are 29 auditors who are used as research samples. The analysis tool uses simple linear regression. The research findings prove that the integrity of auditors in public accounting firms has a significant effect on organizational commitment.